Terorisme dalam Perspektif Hukum Islam - Kasjim Salenda (Universitas Islam Negeri Mataram, 2009)
Terminologically, the term of terrorism is not found in Islamic knowledge treasures. However, terrorism as an action has occurred along the Muslim history. This writing tries to trace concepts that contain meanings of terrorism in Islamic law. Examples of the concepts are al-irhâb (irhâbiyyah), al-hirâbah (robbery), al-baghy (rebellion), qâthi‘ al-tharîq or quththâ‘ al-tharîq (hijacking), and al-‘unf (an antonym of gentleness). Actions meant in such concepts are categorized as terrorism because they bear violence, cause people’s panic, material and physical damage, and have political aims. Such terror actions, even if they are committed based on Jihad order, such as murder, hijacking, bombing, robbery and intimidation are forbidden and can not be legitimized because they are contradictory to Islamic teachings which forbid acts of damaging in the earth, to the principles of al-dlarûriyyât al-khams (preserving five human basic needs), humanity, justice and deliberation in Islam.